The Development of Startup Coop in Indonesia: An Overview Maqashid al-Sharia - Jayusman Jayusman; Efrinaldi Efrinaldi; Muhammad Aulia Rachman; Muhammad Jayus (Justicia Islamica, 2023)
This paper uses the juridical-philosophical method and conceptual approach to develop regulations for cooperative-based startup companies (startup coop) in Indonesia from the perspective of positive law and maqÄsid al-SharÄ«a. This study concludes that the issue of startup coop from the maqashid perspective is considered not contrary to Islamic values, the principles of muamalah, and in harmony with the objectives of the law. Startup Coop is oriented towards creative innovation based on the value of brotherhood and kinship. In addition, startup coops also aim to absorb productive labor and develop human resources from among the younger generation in creative business development. This research contributes to optimizing creative and innovative human resources in line with maqashid ideal goals.